Landscape and the moving image - Elwes, Catherine, 1952- (Intellect, 2022)
New exploration of how the moving image mediates our relationship to and understanding of landscapes. The focus is on artists' film and video and draws on work from the 1970s to the present day. An informed, personal view from a high profile author considering if appreciation of nature's aesthetics undermines commitment to ecology. 30b/w illus.